2017
DOI: 10.1016/j.cardfail.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Epidemiology of Heart Failure to Improve Management Practices: An Asia-Pacific Perspective

Abstract: Heart failure (HF) is a major global healthcare problem with an estimated prevalence of approximately 26 million. In Asia-Pacific regions, HF is associated with a significant socioeconomic burden and high rates of hospital admission. Epidemiological data that could help to improve management approaches to address this burden in Asia-Pacific regions are limited, but suggest patients with HF in the Asia-Pacific are younger and have more severe signs and symptoms of HF than those of Western countries. However, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 87 publications
7
75
0
2
Order By: Relevance
“…This review is focused on the practice of AHF in the USA and Japan for the following reasons: first is the expectation of overlap between the USA and Europe in terms of clinical practice, contrary to that in Japan due to the degree of heterogeneity. Previous literature reviews, with respect to comparison of key pharmacological therapy, reported that there is generally good agreement between the guidelines from North America and Europe . Second, the authors have profound clinical experience in both the USA and Japan but, unfortunately, not in Europe.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This review is focused on the practice of AHF in the USA and Japan for the following reasons: first is the expectation of overlap between the USA and Europe in terms of clinical practice, contrary to that in Japan due to the degree of heterogeneity. Previous literature reviews, with respect to comparison of key pharmacological therapy, reported that there is generally good agreement between the guidelines from North America and Europe . Second, the authors have profound clinical experience in both the USA and Japan but, unfortunately, not in Europe.…”
Section: Introductionmentioning
confidence: 91%
“…Previous literature reviews, with respect to comparison of key pharmacological therapy, reported that there is generally good agreement between the guidelines from North America and Europe. 3,4 Second, the authors have profound clinical experience in both the USA and Japan but, unfortunately, not in Europe. This information may help to identify public health issues within different populations in each country, which can then be targeted with performance improvement initiatives in order to improve outcomes in patients with AHF.…”
Section: Introductionmentioning
confidence: 99%
“…7 Data from global clinical trials and disease registries in the USA, Europe and the Asia-Pacific region highlighted several differences in the demographic and clinical characteristics of HF patients in the Asia-Pacific region compared with patients from Western countries; for example, patients from the Asia-Pacific region were younger, had greater comorbidity burden and received lower-than-recommended levels of treatment. 2, 8 The patient eligibility criteria of PARALLEL-HF were designed to largely follow those of Age (years) ≥20 ≥18 ≥20 ≥55 NYHA class II-IV II-IV II-IV II-IV LVEF (%) ≤35% ≤40% (changed to ≤35%) ≤35% ≤30% (or ≤35%+QRS duration >130 ms on ECG) Natriuretic peptide level NT-proBNP ≥600 pg/mL, or NT-proBNP ≥400 pg/mL+HF hospitalization within 12 months BNP ≥150 pg/mL (NT-proBNP ≥600 pg/mL) or BNP ≥100 pg/mL (NT-proBNP ≥400 pg/mL)+HF hospitalization within 12 months -CV hospitalization 6 months before randomization or BNP ≥250 pg/mL or NT-proBNP ≥500 pg/mL (men) and ≥750 pg/mL (women) within 15 (for the NYHA Class I/II randomized set) were conducted for PARADIGM-HF patients with screening visit data for all the required prognostic variables.…”
Section: Methodsmentioning
confidence: 99%
“…1 India has an estimated prevalence of about 1.3-2.3 million. 2 American Heart Association reports that the lifetime risk of developing HF in men and women at the age of 40 is 1 in 5. 1 Probable etiologies include coronary artery disease, previous episode of myocardial infarction, hypertension, diabetes mellitus, abnormal heart valves (either congenital or disease oriented).…”
Section: Introductionmentioning
confidence: 99%